2018
DOI: 10.1177/1753944718784536
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/valsartan in cardiovascular disease: evidence to date and place in therapy

Abstract: Cardiovascular (CV) disease is a major cause of morbidity and mortality in the developing and the developed world. Mortality from CV disease had plateaued in the recent years raising concerning alarms about the sustained efficacy of available preventive and treatment options. Heart failure (HF) is among the major contributors to the CV-related health care burden, a persisting concern despite the use of clinically proven guideline-directed therapies. A requirement for more efficient medical therapies coupled wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 61 publications
1
16
0
6
Order By: Relevance
“…The PIONEER-HF study (comparison of sacubitril/valsartan versus enalapril on effect on nt-pro-bnp in patients stabilized from an acute heart failure episode), which showed that treatment with sacubitril/valsartan produced a significantly greater reduction in N-terminal pro–B-type natriuretic peptide (NT-proBNP) levels than enalapril without increasing the rates of major adverse events in patients hospitalized with acute decompensated heart failure (Velazquez et al, 2019), may help in overcoming the clinical inertia (Jarcho, 2019). The angiotensin receptor–neprilysin inhibitor (ARNI) has shown considerable cardiovascular benefit and absolute risk reduction compared with the standard-of-care treatment in the PARADIGM (Yandrapalli et al, 2018) and PIONEER-HF (Morrow et al, 2019; Velazquez et al, 2019) trials. The composite endpoint, which was explored as part of a prespecified exploratory analysis, consisted of death, rehospitalization for heart failure (hospital stay >24 hours), requirement for a left ventricular assist device insertion, or listing for a cardiac transplantation.…”
Section: Angiotensin Receptor–neprilysin Inhibitors: a Current Pementioning
confidence: 99%
“…The PIONEER-HF study (comparison of sacubitril/valsartan versus enalapril on effect on nt-pro-bnp in patients stabilized from an acute heart failure episode), which showed that treatment with sacubitril/valsartan produced a significantly greater reduction in N-terminal pro–B-type natriuretic peptide (NT-proBNP) levels than enalapril without increasing the rates of major adverse events in patients hospitalized with acute decompensated heart failure (Velazquez et al, 2019), may help in overcoming the clinical inertia (Jarcho, 2019). The angiotensin receptor–neprilysin inhibitor (ARNI) has shown considerable cardiovascular benefit and absolute risk reduction compared with the standard-of-care treatment in the PARADIGM (Yandrapalli et al, 2018) and PIONEER-HF (Morrow et al, 2019; Velazquez et al, 2019) trials. The composite endpoint, which was explored as part of a prespecified exploratory analysis, consisted of death, rehospitalization for heart failure (hospital stay >24 hours), requirement for a left ventricular assist device insertion, or listing for a cardiac transplantation.…”
Section: Angiotensin Receptor–neprilysin Inhibitors: a Current Pementioning
confidence: 99%
“…Various HF treatments exist and have shown success in reducing HF-associated mortality, such as implantable cardioverter defibrillators, heart transplant surgery, and numerous medications including ones that target the sympathetic nervous system (β-adrenergic receptor blockers), the renin-angiotensin aldosterone system (angiotensin converting enzyme inhibitors and angiotensin II receptor blockers) [ 14 ], and the pacemaker current of the sinoatrial cells (ivabradine) [ 15 ]. Furthermore, medications focusing on dual inhibition of the renin-angiotensin aldosterone system (RAAS) as well as neprilysin blockade [ 16 ] (angiotensin receptor-neprilysin inhibitor) have been shown to cause a significantly greater reduction in CV-related death, HF hospitalizations, and all-cause mortality compared to only RAAS blockade [ 17 ]. However, mortality rates following diagnosis of HF remain high [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Having as a goal to be considered a therapeutic option, the combination sacubitril/valsartan has been studied in a variety of clinical trials [ 71 , 72 ]. Moreover, beneficial effects over renal function have been observed, specifically in diabetic patients with HF and a maximum blockage of RAAS, as demonstrated by Parcker et al .…”
Section: Introductionmentioning
confidence: 99%
“…In order to assess the effectivity of this drug combination in HF, the phenotypes of heart failure with preserved ejection fraction (HFpEF) and reduced ejection fraction (HFrEF) have been considered (Table 1 ) [ 71 ]. PARAMOUNT-HF study was the first to provide clinical data about Sacubitril/Valsartan in patients with preserved (45% or more) left ventricular ejection fraction (LVEF) and also with high serum levels of NT-proBNP, with their primary objective to compare the efficacy and security of an angiotensin receptor-neprilysin inhibitor against an ARB (Valsartan) [ 75 ], noticing a reduction in serum concentrations of this marker in the group of dual therapy, and also showing a similar profile of side effects, independent of their antihypertensive actions [ 76 ].…”
Section: Introductionmentioning
confidence: 99%